Health workers’ perspectives regarding climate change and health in Kween District, Mount Elgon, Uganda – A qualitative study - Aggrey Siya; Akim Tafadzwa Lukwa; Chemutai Faith; Noah Mutai; Plaxcedes Chiwire (The Journal of Climate Change and Health)
Introduction: In Uganda, climate change poses significant threats to human livelihoods by exacerbating existing health challenges and introducing new health threats. This study focused on the knowledge and perspectives of health workers regarding the intersection of health and climate change, with particular emphasis on malaria, a disease prevalent in the country and notably affected by climate variations, especially in fragile mountainous regions such as Mount Elgon. Materials and Methods: This study was conducted in the Kween District of Mount Elgon, Uganda. We utilized qualitative approaches, recruiting health service providers from various altitudinal zones using snowball sampling techniques. Health facilities were selected through purposive sampling and 69 health service providers participated. Data collection involved semi-structured interviews that explored health workers' knowledge of climate change and its impacts on health, including malaria. Results: Health workers perceived an increase in disease occurrences attributed to climate change, affecting their work in terms of load and access to facilities during extreme weather conditions such as heavy rains and heatwaves. Malaria cases were perceived to have increased in the higher altitudes that previously experienced limited case numbers. Despite the difficulties in distinguishing between climate change and climate variability, health workers associated these health-related phenomena with long-term weather alterations. Conclusions: Health workers perceive that climate change is affecting their work and delivery of health services. By leveraging the knowledge and experience of health workers regarding the relationship between health and climate change, there is an opportunity to enhance the resilience of the health system.